2019
DOI: 10.3389/fpsyt.2019.00816
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction and Depression in Chinese Adolescents: A Moderated Mediation Model

Abstract: Research has revealed that Internet addiction is a risk factor for adolescents’ development of depressive symptoms, although the underlying mechanisms are largely unknown. The present study examines the mediating role of positive youth development and the moderating role of mindfulness to determine the association between Internet addiction and depression. A sample of 522 Chinese adolescents completed measures related to Internet addiction, positive youth development, mindfulness, depression, and their backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 81 publications
3
38
0
Order By: Relevance
“…Participants with an IAT score of 39 or below were classified as normal Internet users (NIU), who only had some or no problems controlling Internet use. Adequate reliability of IAT in Chinese languages compared with English (Cronbach alpha≥0.82) ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants with an IAT score of 39 or below were classified as normal Internet users (NIU), who only had some or no problems controlling Internet use. Adequate reliability of IAT in Chinese languages compared with English (Cronbach alpha≥0.82) ( 14 , 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Emotion problems, such as depression (35) and anxiety (36) have been associated with internet addiction, so emotion problems may be risk factors for internet addiction. Expressive suppression may be a risk mediating factor between emotion problems and internet addiction.…”
Section: The Present Studymentioning
confidence: 99%
“…In the context of the key resource theory ( Hobfoll, 2002 ; Thoits, 1994 ) and the broaden-and-build theory of positive emotions ( Fredrickson, 2001 ), individuals with positive psychological resources are prone to being more capable of selecting, altering, and implementing their other resources to decrease mental distress, enabling them to flourish. Numerous studies have demonstrated that adolescents' psychological resources, including emotional intelligence, mindfulness, and resilience, can alleviate their depression symptoms ( Anyan & Hjemdal, 2016 ; Chi et al, 2019 ; Davis & Humphrey, 2012 ). Therefore, character strengths, as an important psychological resource, might be negatively related to adolescents' depression symptoms.…”
Section: Introductionmentioning
confidence: 99%